2020
DOI: 10.3390/diagnostics10070487
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Identification of Down Syndrome Using Facial Images with Deep Convolutional Neural Network

Abstract: Down syndrome is one of the most common genetic disorders. The distinctive facial features of Down syndrome provide an opportunity for automatic identification. Recent studies showed that facial recognition technologies have the capability to identify genetic disorders. However, there is a paucity of studies on the automatic identification of Down syndrome with facial recognition technologies, especially using deep convolutional neural networks. Here, we developed a Down syndrome identification method utilizin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…The distinctive facial characteristics in facemask-wearing conditions provide an opportunity for automatic identification. Recent rapid technological innovations in deep learning and computer vision have presented opportunities for development in many fields [ 9 , 10 ]. As the main component of deep learning methods, deep neural networks (DNNs) have demonstrated superior performance in many fields, including object detection, image classification, image segmentation, and distancing detection [ 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The distinctive facial characteristics in facemask-wearing conditions provide an opportunity for automatic identification. Recent rapid technological innovations in deep learning and computer vision have presented opportunities for development in many fields [ 9 , 10 ]. As the main component of deep learning methods, deep neural networks (DNNs) have demonstrated superior performance in many fields, including object detection, image classification, image segmentation, and distancing detection [ 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the automatic detection of facial features, CNNs have been incorporated into the assisted diagnosis of genetic syndromes. Several studies showed that CNN-based facial recognition models for genetic syndrome diagnosis achieved high accuracy (9)(10)(11)(12). In 2019, Gurovich et al (10)…”
Section: Introductionmentioning
confidence: 99%
“…Based on the automatic detection of facial features, CNNs have been incorporated into the assisted diagnosis of genetic syndromes. Several studies showed that CNN-based facial recognition models for genetic syndrome diagnosis achieved high accuracy ( 9 12 ). In 2019, Gurovich et al ( 10 ) reported a deep CNN framework, DeepGestalt, trained on a dataset of over 17,000 pictures of faces representing more than 200 syndromes.…”
Section: Introductionmentioning
confidence: 99%
“…on the one hand, arti cial intelligence and machine learning methods can quickly and accurately complete the basic data cleaning and large-scale data sorting, and on the other hand, do data mining for massive tongue & pulse data. Different recognition algorithms and machine learning methods have been widely used in image recognition, target detection, natural language processing, and other elds [10][11][12]. Nowadays, breakthroughs have been made in fatigue quanti cation and standardization.…”
Section: Introductionmentioning
confidence: 99%